Seismic analysis of geosynthetic-reinforced retaining wall in cohesive soils - Alhajj Chehade, H.; Dias, D.; Sadek, M.; Jenck, O.; Hage Chehade, F. (Geotextiles and geomembranes, 2019)
Although a cohesionless backfill is recommended for geosynthetic reinforced earth retaining walls, cohesive soil have been widely used in many regions across the globe for economic reasons. This type of backfill exposes the soil to the crack formation that leads to reduce the stability of the system. In this paper, to investigate the internal seismic stability of reinforced earth retaining walls with cracks, the discretization method combined with the upper bound theorem of limit analysis are used. The potential failure mechanism is generated using the point-to-point method. Two types of cracks are considered, a pre-existing crack and a crack formation as a part of the failure mechanism. The use of the discretization method allows the consideration of the vertical spatial variability of the soil properties. A pseudo-dynamic approach is implemented which allows the account of the dynamic characteristics of the ground shaking. The presented method is validated using the conventional limit analysis results of an existing study conducted under static conditions. Once the proposed technique to consider the cracks is validated, a parametric study is conducted to highlight the key parameters effects on the lower bound of the required reinforcement strength.